Colonization by staphylococcus aureus in healthy carriers from a nursery in a university hospital - Santos, Branca Maria Oliveira; Darini, Ana Lúcia Costa (Medicina (Ribeirao Preto), 2002)
The aim of this study was to verify the colonization by Staphylococcus aureus among healthy carriers at a nursery of an University Hospital in Ribeirao Preto — University of Sao Paulo. Bacteriological and molecular characteristics were used to determine epidemiological relationship among isolates. S. aureus isolates were collected (obtained) from nasal swab, right and left hands of 37 mothers (or liable for the children) from hospital staff, that were working from 6 months or more and that were using the nursery for their children during the work time. Thirtynine children and 39 nurses from the nursery were included. A total of 55 S. aureus were isolated, 58,2% from nasal swabs, 20,0% from right hands and 21,8% from left hands, which shows predominance of S. aureus in nasal swabs. Antibiograms showed resistence to 2 or more antibiotics tested. PFGE profiles using Smal and generated dendograms showed low genetic similarity among carriers, mainly among nursery staff and the children. The high genetic similarity was observed among some children and their own mother or liable. Antibiogram was not usefull to determine epidemiological relationship among S. aureus isolates, but the genetic study was very important to delineate and compare S. aureus isolates from carriers.